ANALISIS PERBANDINGAN RISIKO (RISK) DAN TINGKAT PENGEMBALIAN (RETURN) ANTARA DEPOSITO DENGAN EMAS - Salimah, Adilatus (Department of Management, 2018)
The aim of this research is to compare the risk and returns on investment. The most preferred investment of Indonesian society is a low-risk investment. Investment instruments that include low-risk investments which is used in this research are an investment on deposit and investments on gold. Based on the results of the comparison and discussion in this research shows that investment on deposits is give more profit than investment on gold. Although the risk incurred in investment on deposit is higher than investment on gold by a margin of 0.0357 but the rate of return of investment on gold is higher than investment on deposit by a margin of 2.80%. So, with different risk 0.0357 gives the rate of return 2.80% which mean is higher with T-Test shows significant point 0,010.